(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The aim of the research is to identify the health control prevailing among patients with patients with hypertension, and to identify the degree of self-efficacy among patients with hypertension in the city of Lattakia, as well as to identify the relationship between the source of health control and its relationship to their self-efficacy. The descriptive approach was followed, and two measures were used (the health control measure and the self-efficacy measure), which were applied to a sample of (138) male and female patients with patients with hypertension in the city of Lattakia for the year 2021. The results of the research concluded that the degree of health control among patients with hypertension, was meddle, and the internal control came in the first place, followed by the external control of influence, and then in the third place the external control of luck. The degree of self-efficacy among patients with hypertension, was moderate. As well as the existence of an acceptable direct correlation statistically significant relationship between the source of health control and self-efficacy in patients with hypertension, as the results showed the existence of a strong direct statistically significant correlation between internal control and self-efficacy, while the relationship between self-efficacy and each of the external control of influence and external control Fortunately, it was negative and weak. Based on these results, several recommendations were made, the most important of which are: Implementation of counseling programs to raise the level of self-efficacy in patients with hypertension,. Building tutorials programs based on enhancing and strengthening internal control and self-efficacy in patients with hypertension, and conducting studies on the relationship between the source of health control and other variables such as (acceptance of treatment and healthy quality of life) of Patients with Chronic Diseases.